KEPASTIAN HUKUM PARTISIPASI MASYARAKAT DALAM PENERBITAN PERIZINAN DIBIDANG PERTAMBANGAN - Anastasia Pricillia Wibowo (Fakultas Hukum Universitas Narotama, 2023)
This study aims to understand the essence of community participation in various stages of mining business permits. This research method uses a normative method and then analyzed qualitatively with a Legislative and Conceptual approach. Meanwhile, community participation related to their involvement in the issuance of IUPs has not been considered effective as based on Law no. 3 of 2020, Law no. 32 of 2009, PP No. 8 of 2018, PP No. 22 of 2021, Minister of Environment Regulation No. 17 of 2012, as well as laws and regulations related to Amdal or UKL-UPL. In addition, the supervision of the rock mining business permit found environmental damage due to the mining business activity, in addition it was found that there were miners who carried out reclamation outside the mining business permit area and did not meet the criteria for success in the reclamation effort. so that he was ordered to re-do efforts to restore the environment in damaged locations that are within the mining business permit area. Mining business activities carried out without the participation of the surrounding community can cause social, environmental and economic problems for the community. Especially ecological problems that have a huge impact on the community such as floods, abrasion, forest fires, landslides and tornadoes, according to data from the South Sulawesi Walhi, throughout 2019 nearly 1.03 million residents of South Sulawesi were affected by this ecological disaster.Keywords: legal certainty, licensing, mining.